Prediction of Regional Development Bank Ratings based on Financial Risk Factors - Kaparang, Vica W.P.; Lambut, Adventinus K.; Supriyanto, Supriyanto (Journal of Finance and Business Digital, 2024)
The research analyzes predictions of regional development bank ratings, using financial risk factors, namely profitability, asset quality, and capital, each of which uses the ROA ratio, NPL, and the amount of core capital or Tier 1 capital from the bank. As a development by applying similarities from previous research, the current research examines the financial performance of PT Regional Development Bank North Sulawesi Gorontalo during 2019-2023. The results of this research show that by applying equations in bank rating predictions that take into account financial risk factors, BSG received a rating that was different from the actual rating given by the designated rating agency. This research will discuss the prediction results with analysis that focuses more on BSG's own financial performance, especially financial risk factors.